Experimental and Theoretical Investigation of Noise Effect in Centrifugal Fan Impeller (Journal of Engineering, 2014)
In this work a study was made in centrifugal fan blower to investigate the effect of impeller blade design on sound pressure level (SPL). Shroud and unshroud impeller of nine blades are used. The sound generation from flow inside the test rig at different positions was displayed by using spectral analyzer. The experiments were carried out in anechoic chamber with small holes in its walls, under ambient condition about (25-27) C ° to avoid the effect of temperature on the sound pressure level. The results showed that (SPL) decreased with the increase of distance from the source about (3-4)dB when distance varied about (0.8-1.06)m, and the (SPL) decreased with the decrease of velocity about (8-12)dB when velocity varied between (13000-2600) r.p.m., and when the velocity remain constant (SPL) increased with the increased of pressure about (7-15)dB when the pressure varied between (36-8)mbar. For the purpose of comparison, two types of impellers were tested under same conditions, the results showed that (SPL) increased when shroud used on the impeller. The mathematical results show good agreement with the experimental results. The study also concluded a spectral analysis of the noise generated using 1/3 octave band filter. The analysis showed that (SPL) increased with frequency range of (0.8-400) Hz. The maximum sound pressure level was appeared clearly in the frequency range between 200 – 400 Hz .